Realization of the First GaN Based Tunnel Field-Effect Transistor - Chaney, Alexander; Turski, Henryk; Nomoto, Kazuki; Wang, Qingxiao; Hu, Zongyang; Kim, Moon; Xing, Huili Grace; Jena, Debdeep (2018 76th Device Research Conference (DRC), 2018)
Tunnel field-effect transistors (TFETs) offer the means to surpass the subthreshold swing (SS) limit of 60 mV/dec that limits MOSFETs. While MOSFETs rely on modulating a potential barrier, which is subject to a Boltzmann tail in the density of states (DOS), interband tunneling in TFETs enables a sharp turn off of the DOS because the transport is no longer governed by an exponential tail of carriers. These devices have been investigated in Si & III-V material systems 1 , achieving SS's as low as 20 mV/dec 2 . GaN is advantageous to these other material systems because its large bandgap is ideal for suppressing leakage current. Unfortunately impurity doping in GaN alone is not enough to achieve the internal fields required to promote interband tunneling[Fig l(a)]. However, by taking advantage of the difference in polarization fields between InGaN and GaN, a device structure favoring interband tunneling can be made [Fig l(b)]. Li et. al. 3 have theoretically predicted that a GaN heterojunction TFET could obtain an SS of 15 mV/dec and a peak current of 1\times 10^{-4}\ \mathrm{A}/\mu \mathrm{m} . For the work being presented, GaN TFETs were fabricated using a surrounding gate (SG) architecture utilizing both nanowires and fins formed from a top-down approach.